(Re)read The wretched of the earth: Jean-Paul Sartre and Frantz Fanon 58 years later - Raimondi, Edoardo (Itinerari, 2023)
The aim of this contribution is to show the complementarity of Frantz Fanon’s and Jean Paul Sartre’s theories, by considering the colonial reality of their time. The paper is divided into two parts: in the first, I examine Sartre’s preface to Le damnés de la terre (1961) by relating it to the content of L’existentialisme est un humanisme (1946); in the second, I highlight the relations between Fanon’s and Sartre’s theories.